PROBLEMATIKA ORANG TUA DALAM MENDAMPINGI ANAK BELAJAR SECARA DARING DI JORONG KOTO BARU NAGARI AIR DINGIN KECAMATANLEMBAH GUMANTI KABUPATEN SOLOK - Sariwal Afri Doni; Arman Husni, Arifmiboy, Charles (CV. ADIBA ASIHA AMIRA, 2024)
This research is motivated by online learning, namely, Problematics of Parents in Accompanying Children Learning Online, parents have difficulty dividing time between work and accompanying children to learn children's learning compilation with the same working time, parents do not understand the material given by the teacher for Explanation kepadahal this is due to limited knowledge, parents have difficulty in fulfilling children's needs for brave learning such as buying a cellphone for brave learning senses and internet quota. The original question of this research is What are the Problems of Parents in Accompanying Children to Learn Bravely in Jorong Koto Baru Nagari Air Dingin, Lembah Gumanti District, Solok Regency? What are the Negative and Positive Impacts of Parents' Problems in Accompanying Children to Study Bravely in Jorong Koto Baru Nagari Air Dingin, Lembah Gumanti District, Solok Regency? This research uses qualitative research, using qualitative research methods, the source of records obtained through information includes key informants, namely parents of students who study bravely in Jorong Koto Baru Nagari Air Dingin, Lembah Gumanti District, Solok Regency and supporting informants, namely students who study bravely in Jorong Koto Baru Nagari Air Dingin, Lembah Gumanti District, Solok Regency on data collection, using interviews. Analysis of data through information reduction, presentation of records, and verification of information the results of the study show that: (1) parents interpret courageous learning, namely the online learning process accompanied by their respective parents. (2) the negative consequences are that the compilation of parents is taken up, the lack of education of parents results in knowledge that has less passion so that it feels difficult to teach children, less sense of responsibility for children, parents are required to understand technology and increased expenses. the positive impact is that parents have poly compilation with children and understand child development.